The dead guy next door [large type] - Score, Lucy (Score, Lucy. Riley Thorn novels, 2025)
"Riley Thorn is divorced. Broke. Living with a pack of elderly roommates. And those hallucinations she's diligently ignoring? Her tarot card-dealing mom is convinced they're clairvoyant visions. Just when things can't get worse, a so-hot-it-should-be-illegal private investigator shows up on her doorstep looking for one of her neighbors . . . who turns up murdered. Nick Santiago doesn't play well with others. Unless the "others" are of the female persuasion. Wink. He's a rebel, a black sheep, a man who prefers a buffet of options to being stuck with the same entrée every night, if you catch his drift. When the pretty, possibly psychic Riley lands at the top of the list of suspects, Nick volunteers to find out whodunit. Only because he likes solving mysteries-not because he wants to flex his heroic muscles for the damsel in distress. All they have to do is figure out who pulled the trigger, keep a by-the-book detective with a grudge at bay, and deal with a stranger claiming he was sent to help Riley hone her psychic gifts. All before the killer discovers she's a loose end that requires snipping."--